Pendampingan Program Stimulasi Ibu-Anak Cegah Stunting di Posyandu Ngadi Asih Surakarta - Darah Ifalahma; Ana yuliana; Niken Luthfiyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Integrated Health Post (Posyandu) Ngadi Asih Surakarta implements Integrated Primary Services (ILP) services targeting pregnant women, toddlers, and breastfeeding mothers in support of the zero new stunting program. So far, the implementation has been limited to weighing and measuring. Problems have been identified, including the lack of health services and health education on stunting prevention. This is due to the limited knowledge and skills of cadres. The solution is an innovative Mother-Child Stimulation Program to Prevent Stunting (Prosiacting) at the Ngadi Asih Surakarta Posyandu. The activities carried out are Prosiacting Activation and Capacity Building for cadres in the form of training in Pregnancy Exercises, Baby Massage, and Oxytocin Massage. The implementation method has 6 stages: preparation, apperception, application of science and technology, mentoring, evaluation, and termination. The results of the Mother-Child Stimulation Program Innovation to Prevent Stunting (Prosiacting) have been well implemented at the Ngadi Asih Surakarta Integrated Health Post (Posyandu). Capacity Building activities for cadres were carried out well. The knowledge and skills of cadres have increased after the training, namely Pregnancy Gymnastics skills in the good category (75%), Baby Massage skills in the good category (80%), and Oxytocin Massage skills in the good category (90%). The Mother-Child Stimulation Program to Prevent Stunting (Prosiacting) has been activated. Cadres are committed to implementing the results of the training and Prosiacting routinely once a month during the Toddler Family Development activity. With the stunting prevention stimulation skills possessed by cadres, it is hoped that cadres will be able to independently accompany pregnant women, mothers of infants and toddlers, and postpartum mothers. It is hoped that this program will be routinely implemented at the Ngadi Asih Surakarta Integrated Health Post (Posyandu) as an effort to independently prevent Stunting in the Community.